Association of interleukin‐10 gene promoter polymorphisms with recurrent miscarriage: a meta‐analysis. (August 2016) - Su, Duo; Zhang, Yeye; Wang, Qingqin; Wang, Jing; Jiao, Baoquan; Wang, Gang; Wu, Xiaohua
Abstract: Problem: The association between IL‐10 gene promoter polymorphisms and the risk of recurrent miscarriages (RM) remains controversial. The present meta‐analysis was performed to derive a precise estimate of the relationship. Method of study: We searched the PubMed and EMBASE for studies related to the association between the IL‐10 gene polymorphism and the risk of RM. Summary odds ratio (OR) with 95% confidence interval (CI) was estimated to assess the associations. Results: Thirteen studies, including 2047 RM cases and 2055 control samples, were identified. The results showed a significant association between rs1800896, rs1800871 and RM risk (for rs1800896: GA+GG vs AA: OR=1.20, 95% CI=1.04–1.39, P =.02; for rs1800871: CT+TT vs CC: OR=1.64, 95% CI=1.13–2.36, P =.009). No evidence of association was noted between rs1800872 haplotype and RM risk. Conclusion: IL‐10 gene promoter polymorphisms, rs1800896 and rs1800871, play a potential role in increasing the risk of RM.